ANALISIS KINERJA KEUANGAN PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA PERIODE 2020-2022 - Devi, Shinta; Komala, Fatma Sri; Zahro, Sifa Alfiatul; Dael, Ayu Renovasi; Daeli, Anis Kristin; Endarwati, Endarwati (Program Studi Manajemen, 2023)
This study aims to determine the financial performance of the five largest PT in Indonesia in 2020-2022 using the analytical method of Liquidity Ratios, solvency ratios, activity ratios and profitability ratios. The data used in this study are the balance sheets of the five largest PTs in the food and beverage sub-sector as of 31 December 2020-2022 and the profit and loss statements of the five largest PTs in the food and beverage sub-sector in the last year 31 December 2020-2022. The data analysis method used is descriptive analysis method with a quantitative approach. From the analysis carried out on the financial statements for the last three years, it shows that the company's performance has fluctuated or changed. This is because the five largest companies were affected by Covid-19.